Abscisic acid and methyl jasmonic acid module anthocyanins and trans-resveratrol accumulation in berry skin of five red Vitis vinifera cvs. in two contrasting viticultural regions of Mendoza-Argentina. - Malovini, Emiliano (2019)
Fil: Malovini, Emiliano. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina.